Jose Romero: capstone - Romero, Jose, artist (Colorado State University. Libraries, 2024)
The artist's statement: My scope when it comes to my graphic design practice has to do with ideas of escapism and relief from the modern and minimalist design trends. I believe that as the world becomes more corporate, design is becoming more dull and therefore, starts to lack personality and soul. Through my design, I am hoping to achieve a language that reads as joyful and that inspires people to be more happy, bright, as well as creative.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design